Plumbagin inhibits invasion and migration of breast and gastric cancer cells by downregulating the expression of chemokine receptor CXCR4 - Manu, K.; Shanmugam, M.; Rajendran, P.; Li, F.; Ramachandran, L.; Hay, H.; Kannaiyan, R.; Swamy, S.; Vali, S.; Kapoor, S.; Ramesh, B.; Bist, P.; et al. (BioMed Central Ltd., 2011)
Background: Increasing evidence indicates that the interaction between the CXC chemokine receptor-4 (CXCR4) and its ligand CXCL12 is critical in the process of metastasis that accounts for more than 90% of cancer-related deaths. Thus, novel agents that can downregulate the CXCR4/CXCL12 axis have therapeutic potential in inhibiting cancer metastasis.Methods: In this report, we investigated the potential of an agent, plumbagin (5-hydroxy-2-methyl-1, 4-naphthoquinone), for its ability to modulate CXCR4 expression and function in various tumor cells using Western blot analysis, DNA binding assay, transient transfection, real time PCR analysis, chromatin immunoprecipitation, and cellular migration and invasion assays.Results: We found that plumbagin downregulated the expression of CXCR4 in breast cancer cells irrespective of their HER2 status. The decrease in CXCR4 expression induced by plumbagin was not cell type-specific as the inhibition also occurred in gastric, lung, renal, oral, and hepatocellular tumor cell lines. Neither proteasome inhibition nor lysosomal stabilization had any effect on plumbagin-induced decrease in CXCR4 expression. Detailed study of the underlying molecular mechanism(s) revealed that the regulation of the downregulation of CXCR4 was at the transcriptional level, as indicated by downregulation of mRNA expression, inhibition of NF-?B activation, and suppression of chromatin immunoprecipitation activity. In addition, using a virtual, predictive, functional proteomics-based tumor pathway platform, we tested the hypothesis that NF-?B inhibition by plumbagin causes the decrease in CXCR4 and other metastatic genes. Suppression of CXCR4 expression by plumbagin was found to correlate with the inhibition of CXCL12-induced migration and invasion of both breast and gastric cancer cells.Conclusions: Overall, our results indicate, for the first time, that plumbagin is a novel blocker of CXCR4 expression and thus has the potential to suppress metastasis of cancer. © 2011 Manu et al; licensee BioMed Central Ltd.